Core Needle Biopsy Can Early and Precisely Identify Large Thyroid Masses - Matrone, Antonio; De Napoli, Luigi; Torregrossa, Liborio; Aghababyan, Aleksandr; Papini, Piermarco; Ambrosini, Carlo Enrico; Cervelli, Rosa; Ugolini, Clara; Basolo, Fulvio; Molinaro, Eleonora; Elisei, Rossella; Materazzi, Gabriele (Frontiers in Oncology, 2022)
Background Large thyroid masses, particularly if rapidly growing, are often characterized by compression and infiltration of the vital structures of the neck. Therefore, an early and precise diagnosis, not only of malignancy but also of histotype, is mandatory to set up the right therapy. The aim of this study was to evaluate the diagnostic performance of fine needle aspiration cytology (FNAC) and core needle biopsy (CNB) in this setting. Patients and methods We prospectively evaluated 95 patients with large and rapidly growing thyroid masses admitted to the University Hospital of Pisa, between April 2014 and January 2020. All patients were submitted to FNAC and CNB in the same session. The ability of both procedures to diagnose the malignancy of the lesions, particularly the histotype, and to obtain sufficient material to perform molecular analysis, was evaluated. Results FNA obtained adequate tumor sample to reach a diagnosis in 76/95 (80%) patients, while a higher percentage was obtained with CNB (92/95 – 96.8%). FNAC was able to identify the malignancy of the lesion in 74/95 (77.9%) cases but in only 16/74 (21.6%) cases it was able to define the histotype. CNB was able to define the malignancy of the lesion in all but 3 cases (92/95 – 96.8%) and in all specimens, the histotype was identified. Moreover, in all cases the material extracted from CNB was optimal to perform molecular analysis. No surgical related complications were experienced with both the procedures. Conclusions CNB is a rapid and safe procedure with higher performance compared to FNAC in identifying the histotype of large and rapidly growing thyroid masses. Moreover, adequate material can be obtained to characterize the molecular profile for treating potentially lethal cancers. Then, in the era of precision medicine, CNB should be introduced in the routine clinical practice as a key procedure for an early diagnosis and therapy of these diseases.